Mechanisms, roles and consequences of governance emerging issues - Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Studies in public and non-profit governance ;, 2014)
This 2nd volume of the series builds on the themes of volume 1. Established concepts and theoretical issues are presented by established scholars in the governance, management and administration fields. These are set alongside highlighted emerging themes, and they're practicality illustrated through specific case examples.